Pre-Operative Patient Preparation: Adherence to Hospital Guidelines at Shalamar Hospital Lahore - AQIL HAREEM BUTT,; AFAQ AHMAD,; MUHAMMAD UMAR ABBAS,; LUBNA LIAQUT,; MUHAMMAD USMAN KHAN,; AFIFA ASIF KHAN, (Pakistan Journal of Medical & Health Sciences, 2025)
Objectives: To determine the pre-operative patient’s preparation adherence to hospital guide lines at Shalamar Hospital, Lahore. Materials and Methods: This retrospective study was conducted in preoperative patient’s preparation of general surgery, urology and orthopedic from the record room of Shalamar Hospital, Lahore. The study duration was 6 months (August 2023 to January 2024). Then collected data had been checked, entered and exported to SPSS25.0 version for data analysis. Results: A total of 133 patients (82 males and 51 females) were recruited for this study; with Mean + SD of age (40.93% +14.232). The questionnaire performa filled by researcher himself. In total of 133 patients, 116(87.21%) patients were completely achieved pre-operative preparation adherence to hospital guidelines. 72(93.56%) of general surgery patients follow pre-op guidelines, 22(88%) of urology patients follow up pre-op guidelines and 22(70.96%) of orthopedics patients follow up pre-op guidelines. Conclusion: Patients of general surgery had highest score regarding to preoperative preparation followed by urology and orthopedics surgery had least score regarding to preoperative preparation adherence to guidelines.